PENGARUH LEADERSHIP AUTONOMY SUPPORT DAN MEDIASI KREATIVITAS INDIVIDU TERHADAP PERILAKU INOVATIF - Erni Taruli Pebrina (Universitas Insan Pembangunan Indonesia, 2021)
This study focuses on innovation by individual employees. This study aimed to measure the effect of leadership autonomy support (LAS) on individual innovative behavior (IIB) of manufacturers’ employees in Tangerang which are mediated by individual creativity (IC). Data collection was done by simple random sampling to the employees of a packaging industry in Tangerang. The returned and valid questionnaire results were 98 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that leadership autonomy support have a positive and significant effect on the individual innovative behavior, both directly and indirectly through mediating individual creativity. This new research proposed a model for building individual innovative behavior among the manufacturers’ employees in Tangerang through enhancing leadership autonomy support with individual creativity a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.Kata Kunci : Individual creativity, individual innovative behavior, industrial revolution 4.0, leadership autonomy support.